2019
DOI: 10.5380/rf.v49i3.60013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Indicators and Cost of World Class Maintenance (Wcm) in Forest Machines

Abstract: The study was carried out at a forest company located in the Paraná State, Brazil, with the feller buncher, skidder and harvester. The following indicators were evaluated: mechanical availability, mean time between failures, mean time to repair, proactive maintenance index and maintenance costs, based on data obtained over a period of 18 months, contemplating the stages of implantation, maturation and stabilization of the WCM. The results showed an increase in the mechanical availability of the cutting and ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The overall forest machinery cost was estimated from 20% to 60%, depending on different factors such as machinery age, usage, operator experience, vegetation, weather condition during the production, maintenance strategy etc. [18][19][20][21][22][23][24]. The right maintenance plan, enhancing decision-making in maintenance, and performing work properly can cause cost reductions, boost efficiency, and advance vehicle reliability.…”
Section: Forest Machinery Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…The overall forest machinery cost was estimated from 20% to 60%, depending on different factors such as machinery age, usage, operator experience, vegetation, weather condition during the production, maintenance strategy etc. [18][19][20][21][22][23][24]. The right maintenance plan, enhancing decision-making in maintenance, and performing work properly can cause cost reductions, boost efficiency, and advance vehicle reliability.…”
Section: Forest Machinery Maintenancementioning
confidence: 99%
“…Although some research [17] ignored the effect of maintenance and downtime cost in productivity of machinery during the operation, others estimated the costs associated with forest machinery maintenance (e.g., feller-buncher, forwarder, skidder, processor etc.) vary between 20% and 60% [18][19][20][21][22][23][24] of overall costs. In 2019, Spinelli et al [18] indicated that chipper repair and maintenance may represent between 1.5% and 29% of total production cost.…”
Section: Introductionmentioning
confidence: 99%